ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN AKUNTANSI KELAS XI IPS DI SMA NEGERI 2 LAMONGAN - ANDIKA W, VIKY (Jurnal Pendidikan Akuntansi (JPAK), 2013)
SMA Negeri 2 Lamongan is a favorite school that much demand, so that this school needs to maintain and improve the quality of education. One is through the use of appropriate learning media, engaging and in accordance with the criteria in the learning process. In reality the use of learning media to assist in the learning process and facilitate the learning process. This research aims to determine the learning media that is used by the teacher, and to know the reasons that teachers choose learning media and determine the feasibility of the media. This research is a descriptive, the research subject were accounting subject teacher. Data collection techniques in this research using experts examine sheet, are distributed to the two researchers medium of learning expert, documentation obtained from the school, and interview techniques directly to the accounting subject teacher XI social class. In this research material information that had been obtained were analyzed descriptively. The percentage feasibility of learning media obtained by calculation according to the formula Likert scale. Research results show that accounting subject teacher XI social class using visual media projections a microsoft office powerpoint program that assisted with tools LCD Projector. The results of the feasibility examine calculations showed that the learning media percentage of the feasibility for SK-I/KD-I by 78,57%, SK-I/KD-II by 72,14%, SK-I/KD-III by 63,21%, SK-I/KD-IV by 73,93%, SK-I/KD-V by 76,79%, SK-II/KD-I by 64,29%, SK-II/KD-II by 71,43%. Average percentage of the overall the feasibility score amounted to 71.48%. with decent category. Keywords: Learning Media, Feasibility, Accounting